2011
DOI: 10.1002/pssc.201100277
|View full text |Cite
|
Sign up to set email alerts
|

Low noise high responsivity InAs electron avalanche photodiodes for infrared sensing

Abstract: Dark current measurements on SU‐8 passivated InAs avalanche photodiodes (APDs) were carried out at temperatures ranging from 77 to 290 K. Extraction of the bulk and surface components suggested that the InAs APDs exhibit diffusion dominated bulk current and generation‐recombination surface current. The activation energies obtained were 0.36 eV and 0.18 eV for bulk and surface components respectively. The responsivities of the InAs APDs were measured for wavelengths between 1.3 to 2 µm and the quantum efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
2
15
1
Order By: Relevance
“…13. Similar to the report in [4], for a given bias voltage the multiplication gain decreases significantly at 77 K, which is opposite to most III-V semiconductors. The gain difference between the structure in [4] and the graded structure here are much smaller at 77 K than at 300 K. This is consistent with the conclusion in Ref.…”
Section: A Dark Currentsupporting
confidence: 84%
See 4 more Smart Citations
“…13. Similar to the report in [4], for a given bias voltage the multiplication gain decreases significantly at 77 K, which is opposite to most III-V semiconductors. The gain difference between the structure in [4] and the graded structure here are much smaller at 77 K than at 300 K. This is consistent with the conclusion in Ref.…”
Section: A Dark Currentsupporting
confidence: 84%
“…Similar to the report in [4], for a given bias voltage the multiplication gain decreases significantly at 77 K, which is opposite to most III-V semiconductors. The gain difference between the structure in [4] and the graded structure here are much smaller at 77 K than at 300 K. This is consistent with the conclusion in Ref. [7], where it was found that unlike at room temperature, at 77 K a thicker depletion region does not result in higher gain because the electron ionization coefficient has stronger dependence on electric field at 77 K. Therefore at 77 K, the gain of the graded structure reported here is only comparable to the gain reported in Ref.…”
Section: A Dark Currentsupporting
confidence: 84%
See 3 more Smart Citations